PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU SUMBER DAYA GURU DI SMP NEGERI 8 SAROLANGUN - Lovedly, Syarif (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2024)
The objective of this research is to understand the role of the headmaster in enhancing the quality of teacher resources at SMP Negeri 8 Sarolangun. This study was conducted over a period of 4 months, from August 2024 to December 2024, using a descriptive qualitative method with the headmaster as the key respondent and 3 teachers as additional respondents. Data collection in this research was carried out using interview techniques, observation, and documentation, while data analysis techniques included domain analysis, taxonomic analysis, and componential analysis. Based on the research findings, information was obtained regarding the role of the school principal in improving the quality of teacher resources at SMP Negeri 8 Sarolangun, which includes: (1) holding regular meetings, (2) assigning additional tasks and responsibilities to each teacher beyond teaching activities, and (3) supervising teachers during the teaching and learning process.